2000
DOI: 10.1126/science.287.5451.308
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid Evolution of a Geographic Cline in Size in an Introduced Fly

Abstract: The introduction and rapid spread of Drosophila subobscura in the New World two decades ago provide an opportunity to determine the predictability and rate of evolution of a geographic cline. In ancestral Old World populations, wing length increases clinally with latitude. In North American populations, no wing length cline was detected one decade after the introduction. After two decades, however, a cline has evolved and largely converged on the ancestral cline. The rate of morphological evolution on a contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
661
5
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(698 citation statements)
references
References 40 publications
23
661
5
2
Order By: Relevance
“…The establishment of clines is a feature of many species invasions and has been interpreted as a hallmark example of adaptive evolution in action (Johnston & Selander, 1964;Lacey, 1988;Weber & Schmid, 1998;Huey et al, 2000;Kollmann & Banuelos, 2004;Maron et al, 2004Maron et al, , 2007Leger & Rice, 2007;Etterson et al, 2008;Montague et al, 2008). In our study, divergence was often observed in excess of the neutral expectation generated by ancestry, offering particularly strong evidence that the clines are adaptive.…”
Section: Climate Adaptation Of Silene In Europe and North Americamentioning
confidence: 57%
See 2 more Smart Citations
“…The establishment of clines is a feature of many species invasions and has been interpreted as a hallmark example of adaptive evolution in action (Johnston & Selander, 1964;Lacey, 1988;Weber & Schmid, 1998;Huey et al, 2000;Kollmann & Banuelos, 2004;Maron et al, 2004Maron et al, , 2007Leger & Rice, 2007;Etterson et al, 2008;Montague et al, 2008). In our study, divergence was often observed in excess of the neutral expectation generated by ancestry, offering particularly strong evidence that the clines are adaptive.…”
Section: Climate Adaptation Of Silene In Europe and North Americamentioning
confidence: 57%
“…Any effect of hitchhiking would tend to make our test for adaptation more conservative, as some of the putatively neutral variance controlled for may be linked to regions under selection. Our approach should be complementary to other methods of inferring robust evidence for clinal evolution, such as the observation of coincident parallel clines reported for several species invasions (Huey et al, 2000;Leger & Rice, 2007;Maron et al, 2007). Our method could be especially useful in this context, by controlling for colonization history that might otherwise obscure a parallel cline.…”
Section: Climate Adaptation Of Silene In Europe and North Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative analyses of phenotypic plasticity in laboratory experiments (Atkinson, 1994) and genetic variation along latitudinal clines (Huey et al., 2000) established that most ectotherms mature at larger sizes in colder environments. This phenotypic plasticity has been considered a product of physical constraints as well as natural selection (Angilletta et al., 2004; Atkinson & Sibly, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…At a large geographic scale, such as across a continent, ecological and climatic factors vary greatly among regions, promoting the evolution of specific phenotypes adapted to these specific local conditions (Huey et al 2000). Local adaptation requires populations to differ genetically (Blanquart et al 2013), potentially leading to speciation even in the presence of gene flow (Barton 2010).…”
Section: Introductionmentioning
confidence: 99%